Basilar artery perforator aneurysms: Report of 9 cases and review of the literature. (May 2019) - Bhogal, P.; AlMatter, M.; Hellstern, V.; Pérez, M. Aguilar; Lehmberg, J.; Ganslandt, O.; Bäzner, H.; Henkes, H.
Highlights: A high degree of suspicion is required to detect basilar artery perforator aneurysms. Repeat catheter angiography and 3D rotational angiography should be performed. There is a low risk for re-haemorrhage and perforator infarction with flow diversion. Flow diversion appears a safe and viable treatment option. Abstract: Basilar perforator artery aneurysms (BAPA's) are an under-recognised cause of sub-arachnoid haemorrhage (SAH). We present our single centre experience of BAPA's and review of the literature. We performed a retrospective review of our prospectively maintained database to identify all BAPA's that presented acute SAH between February 2009 and February 2018. We identified 9 patients (male = 7), each with a single aneurysm, and average age 55 ± 9.7 years. All aneurysms were small, 2.1 ± 0.5 mm (range 1–3 mm). Three aneurysms were not detected on initial angiography. Six aneurysms were treated with flow diversion, 3 were managed conservatively. No repeat haemorrhage occurred in the flow diverted patients. One patient treated conservatively suffered a repeat haemorrhage and died (mRS 6). Follow up imaging (n = 7), at average 5.6 months (range 3–12 months), showed complete occlusion in all the flow-diverted aneurysms and no change in one conservatively managed patient. There was no evidence of perforator infarction on the follow-up post treatment imaging. Clinical follow-up data was available in 8 patients, 6 of whom (75%) had a good outcome (mRS ≤ 2). A high index of suspicion is required to diagnose BAPA. Flow diversion can be used to treat BAPA's with acceptable risk of perforator infarction and low risk of repeat haemorrhage.